2013
DOI: 10.4049/jimmunol.1201976
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Dengue Virus Nonstructural Protein 1 Antibodies Cause NO-Mediated Endothelial Cell Apoptosis via Ceramide-Regulated Glycogen Synthase Kinase-3β and NF-κB Activation

Abstract: Immunopathogenetic mechanisms of dengue virus (DENV) infection are involved in hemorrhagic syndrome resulting from thrombocytopenia, coagulopathy, and vasculopathy. We have proposed a mechanism of molecular mimicry in which Abs against DENV nonstructural protein 1 (NS1) cross-react with human endothelial cells and cause NF-κB–regulated immune activation and NO-mediated apoptosis. However, the signaling pathway leading to NF-κB activation after the binding of anti-DENV NS1 Abs to endothelial cells is unresolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 69 publications
(115 reference statements)
0
28
0
Order By: Relevance
“…Studies have shown that this cross-linking leads to high NO production, which increases the production of pro-apoptotic proteins, such as p53 and Bax, and decreases Bcl-2 and Bcl-xL. This increased apoptosis of endothelial cells was correlated directly with the severity of infection [37,38].…”
Section: Deleterious Effects Of No In Viral Infectionsmentioning
confidence: 75%
“…Studies have shown that this cross-linking leads to high NO production, which increases the production of pro-apoptotic proteins, such as p53 and Bax, and decreases Bcl-2 and Bcl-xL. This increased apoptosis of endothelial cells was correlated directly with the severity of infection [37,38].…”
Section: Deleterious Effects Of No In Viral Infectionsmentioning
confidence: 75%
“…Passive transfer of anti-DENV NS1 Abs or active immunization with NS1 can protect mice from DENV challenge 25 , 27 29 . However, several Abs against NS1 show molecular mimicry with host proteins and can cross-react with platelets, endothelial cells and coagulation factors, causing platelet dysfunction, endothelial cell damage and hemorrhage 22 , 30 32 . These factors hinder the development of a potential NS1-based vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…GSK-3β has been reported as a pro-apoptotic protein in various cell types343536. A genetic approach was used to investigate the essential role of GSK-3β in ZA-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%